PROFILING OF ANTHROPOMETRIC, BODY COMPOSITION, AND PHYSICAL FITNESS IN INDIVIDUALS WITH DISABILITIES USING THE MALAYSIA INSPIRE I-TALENT MANUAL - Mojiin, Willince; Othman, Norhasmira; Ahmad, Nur Syamsina; Ghafar, Rosniwati; Hamzah, Nurul Azuar; Zulkifli, Erie Zuraidee (The Indonesian Journal of Public Health, 2025)
Introduction: People with ID were reported prone to be overweight (22.5%) and obese (23.8%) compared to the general population and demonstrated poor level of physical fitness. Aims: This study aims to identify the anthropometric measurement and physical fitness profile in individuals with intellectual disability (ID) and examine the best factors that significantly contribute to explosive strength and balance performance. Method: 124 individuals with ID in Kelantan were recruited in this study. Anthropometry, body composition, and physical fitness were measured using Inspire i-Talent manual. Results: Individuals with ID in this study were overweight (24.27 kg/m2) and their fitness levels were considered generally poor. Stepwise regression analysis revealed that lower limb explosive power variable (R= 0.864, R2= 0.747, F= 34,947, p<0.05) can be anticipated from medicine ball throw, fat percentage and 505 agility test values. In addition, for upper body explosive power  (R= 0.863, R2= 0.745, F= 4.223, p= 0.042) it can be forecasted from standing long jump, body weight, gender, static balance, and arm span. Lastly, standing long jump and 505 agility tests could be the main predictor of static balance (R= 0.597, R2= 0.356, F= 6,586, p= 0.011). Conclusion: Present finding can be used as a reference for researchers in Malaysia when prescribing and implementing physical assessment in ID population.